2002
DOI: 10.5194/angeo-20-1699-2002
|View full text |Cite
|
Sign up to set email alerts
|

Cluster magnetic field observations at a quasi-parallel bow shock

Abstract: Abstract. We present four-point Cluster magnetic field data from a quasi-parallel shock crossing which allows us to probe the three-dimensional structure of this type of shock for the first time. We find that steepened ULF waves typically have a scale larger than the spacecraft separation (∼400-1000 km), while SLAMS-like magnetic field enhancements have different signatures in |B| at the four spacecraft, suggesting that they have a smaller scale size. In the latter case, however, the angular variations of B ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 25 publications
4
55
0
Order By: Relevance
“…Some of them have a whistler packet attached. Shocklets have δB/B 0 < 2 with scale sizes comparable to the "30 second waves", i.e., up to a few R E (Hoppe et al 1981;Le and Russell 1994;Lucek et al 2002). The "discrete wave packets" associated with shocklets have wavelengths of 30 to 2100 km and propagation angles with respect to the magnetic field of approximately 20…”
Section: Shocklets and Slamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of them have a whistler packet attached. Shocklets have δB/B 0 < 2 with scale sizes comparable to the "30 second waves", i.e., up to a few R E (Hoppe et al 1981;Le and Russell 1994;Lucek et al 2002). The "discrete wave packets" associated with shocklets have wavelengths of 30 to 2100 km and propagation angles with respect to the magnetic field of approximately 20…”
Section: Shocklets and Slamsmentioning
confidence: 99%
“…One of the possible explanations is that they grow due to the nonlinear interaction of compressive ULF waves with gradients in the diffuse ion densities (see, for example, Scholer et al 2003;Tsubouchi and Lembège 2004). SLAMS have smaller scale sizes than shocklets and ULF waves (Lucek et al 2002). According to Lucek et al (2004b, their scale sizes are 1000 km and ∼1300 km parallel to the shock normal and tangential to the shock surface, respectively.…”
Section: Shocklets and Slamsmentioning
confidence: 99%
“…The foreshock is most pronounced for a high Mach number bow shock, and when the upstream magnetic field is aligned with the solar wind velocity, i.e., during radial interplanetary magnetic field (IMF) . Some of the foreshock waves can steepen into larger structures, such as Large Amplitude Magnetic Structures (SLAMS), that convect back to the bow shock and modify it (Schwartz, 1991;Lucek et al, 2002Lucek et al, , 2008. Satellite observations and simulation studies have led to the picture of quasi-parallel shock being a patchwork of structures that vary in space and time (e.g., Greenstadt et al, 1982;Gosling et al, 1989;Onsager et al, 1990;Schwartz and Burgess, 1991;Omidi et al, 2005Omidi et al, , 2009Blanco-Cano et al, 2006.…”
Section: Introductionmentioning
confidence: 99%
“…An earlier paper described the first Cluster observations of SLAMS when the tetrahedron scale was ∼600 km (Lucek et al, 2002). This study was limited by the observation of only a few well developed quasi-parallel shocks, but analysis of a small number of SLAMS-like features showed that although all four spacecraft typically encountered each structure, significant differences were seen in the magnetic field profiles at the four spacecraft.…”
Section: Introductionmentioning
confidence: 99%